Russia as a providential force in the propaganda of the central states during the Great War - Żakowska, Magdalena (Myths and Stereotypes in the Collective Representations, 2019)
The purpose of this article is to trace the ambiguous images of Russia which had been presented after October Revolution in propaganda of Central Powers. Because of the Bolsheviks’ peace slogans this country suddenly became the most desired ally of Germany, Austria-Hungary and Bulgaria. The autor aims to answer the following questions: – Which narratives connected to Russia did dominate in German society in 1917–1918? – To which extent were they similar and in which different from the leading narratives in such countries as Austria-Hungary and Bulgaria? – What was the background of the mentioned narratives and images? The author distinguished two major motifs connected to the image of Russia as a kind of providential force: 1) of Russia-the-Saviour (as an exemplification of the myth of “Grandpa Ivan“), 2) of Russia-a-fighter-for-peace (as a continuation of the myth of Russian Revolution).